The Study of Reduplication and Retriplication in the Yoruba Language - Joseph Omoniyi Friday-Otun (Journal of Language and Literature, 2021)
The Yoruba language, a regional lingua franca in Nigeria, which belongs to the Kwa sub-family of Kordofanian phylum of the larger African language family, is spoken in Nigeria, Togo, Ghana, Liberia, Brazil, Cuba, etc. The language attests a very productive feature of reduplication which has attracted the attention of many scholars. But its extended form, tagged, “retriplication” in this paper, remains largely unexplored. This study examines the form and functions of reduplication and retriplication which are two morphological processes where the former serves as a pedestal to the latter. While applying the participant observation method to elicit data from main Yoruba cities in Nigeria, the Pulleyblank (2009) model, as well as the descriptive and context usage approaches are employed to analyse and discuss the data. The study reveals that while reduplication process actualises intensification, nominalisation, emphasis and comparative qualifying, retriplication serves for more intensification, wider nominalisation, more emphasis and superlative qualifying. The research further reveals that, while all cases of verb and adjective reduplicates can be retriplicated without generating unacceptable utterances in Yoruba, the gerundive reduplicates cannot culminate in retriplication. However, kinship reduplicate allows retriplication when stretched to the third generation.  The paper concludes by calling for more study on retriplication in other languages of the world, particularly, African and Asian languages that massively exhibit the two phenomena.